Achieving superior low-temperature superplasticity for lamellar microstructure in nugget of a friction stir welded Ti-6Al-4V joint. (September 2016) - Wu, L.H.; Xue, P.; Xiao, B.L.; Ma, Z.Y.
Abstract: A low-temperature superplasticity of 442% was achieved at 650 °C for a fully lamellar microstructure in the nugget of friction stir welded Ti-6Al-4V joint. More importantly, the nugget showed a comparable superplasticity > 395%) to the base material at 800 °C and 1 × 10 − 4 1 × 10 − 3 s − 1 ; especially at 3 × 10 − 4 s − 1, both the elongation and flow stress of the nugget were similar to those of the base material, which provides the possibility of uniform superplastic forming of the entire weld. Good superplasticity in the lamella-structured nugget was mainly attributed to gradual globularization of the fine lamellae during static annealing and superplastic deformation. Graphical abstract: